Revisiting the Population Genetics of Human Height - Rotwein, Peter (J Endocr Soc, 2020)
CONTEXT: Recent advances in genetics and genomics present unique opportunities for enhancing knowledge of human physiology and disease susceptibility. An outstanding example of these new insights may be seen in the study of human height, of which it has been estimated that approximately 80% is genetically determined. Over the past decade, large-scale population analyses have led to the identification of novel variation in genes and loci individually associated with changes in adult height of as much as 2 cm. OBJECTIVE: To assess these same variants in the genomes of 213 158 individuals compiled by the Genome Aggregation Database (GnomAD) consortium, representing different population groups from around the world. RESULTS: The majority of these height-changing alleles are substantially less prevalent in GnomAD than found previously in other cohorts, with 4 of 5 amino acid substitution variants with the largest impact on adult height being more frequent in the European population than in other groups. CONCLUSIONS: A larger-scale analysis of individuals from diverse backgrounds will be necessary to ensure a full and accurate understanding of the genetic underpinnings of human height throughout the world, and additional studies will be needed to discern the biochemical and molecular mechanisms governing the physiological processes that explain how these variant proteins might selectively impact the biology of the growth plate. Broader understanding of the genetics of height also should set the stage for more comprehensive investigation into the causes of prevalent polygenic human diseases.